Analisis Kerusakan Perkerasan Ruas Jalan Mengunakan Metode Bina Marga - Situmeang, M Hasudungan; Amalia, Amalia; Sriana, Tety (Center for Research and Community Service (LPPM) University of Abulyatama, 2025)
The Teuku Nyak Arief Cemetery Road Section of Aceh Besar Regency is a provincial road that connects Krung Barona Jaya District and Syiah Kuala District with a road length of 4,378 meters and a width of 6 meters which stretches from the cot iri bridge to the lamnyong bridge, The condition of the road section currently has some damage this is certainly very disturbing to road users who pass through the road section. The purpose of this research is to identify road pavement damage including the type and level of damage so that the value of pavement conditions and alternative handling of road damage can be known using the Bina Marga Method. This method reviews the volume of traffic and the type of damage that occurs on the pavement. The evaluation results show that the damage that occurs on the road section includes grain release 41.00%, damage area 1664.29 m2, crocodile skin cracks 31.89% damage area 1296.60 m2, holes and patches 13.80%, damage area 561.07 m2, collapse 10%, damage area 408.01 m2, random cracks 3.06%, damage area 125.59 m2, longitudinal cracks 0.15%, damage area 5.88 m2, transverse cracks 0.10%, damage area 3.70 m2,. The UP value on the Makam Teuku Nyak Arief Road Segment of Aceh Besar Regency is categorized in moderate condition, so it needs serious handling from the government / authorized agencies to immediately make improvements so that the carrying capacity of the pavement can be restored to conditions in accordance with the plan.